Beholding and becoming : the art of everyday worship - Chou Simons, Ruth (Harvest Hourse Publishers, 2019)
You are in the process of becoming. Every day is an opportunity to be shaped and formed by what moves your heart...drives your thoughts...captures your gaze. Is it any wonder that where you direct your eyes and your heart matters in your day-to-day? We become what we behold when we set our hearts and minds on Christ and His redemption story here in the details of our daily lives. Not just on Sunday, not just on holidays, not just when extraordinarily hard or wonderful things happen...but today.